Motivating Engagement with Literature: Using the Individual Story Ending (ISE) Method to Reveal Personal Reading Experiences - Aerila, Juli-Anna (John Wiley & Sons, 2025)
The Individual Story Ending (ISE) is an effective and appealing activity for students of every age. The method requires students—as a group or individually—to devise an ending to an excerpt at a turning point in a fictional narrative. Students can read the excerpt themselves, or the teacher can read it aloud to everyone. The ISE method can be applied to any creative activity and can be developed in various ways. While most teachers already use ISEs, this article suggests ways of building an entire learning process around the method and how ISEs can be used to initiate reading engagement and discussion of different themes.